Engaging domestic users on demand response for heating cost reduction with a recommendation tool: Case study in Belgrade. (June 2022) - Eguiarte, O.; de Agustín-Camacho, P.; Garrido-Marijuan, A.; Vukovic, M.; del Portillo, L.; Romero-Amorrortu, A.
Abstract: The European Union has established a legislative framework that aims to enable consumers and businesses to take information-based decisions to save energy and money. Additionally, the increase of Distributed Energy Resources (both on generation and consumption) requires additional efforts to maintain the reliability and stability of the electric grid and the need of flexibility from residential buildings. The present study introduces a domestic decision support tool for reducing heating costs. This app provides detailed recommendations to end-users based on the day-ahead hourly weather forecast, electric and district heating tariffs predictions, heating demand, and heating systems dynamic performance. The tool was tested in 6 dwellings of a neighborhood of Belgrade during the last months of 2021 heating season (March–May). Energetic results suggest that 40% of participants followed the given recommendations and changed their heating pattern. Additionally, survey results show that end-users found the lack of information and knowledge as the main barrier to actively participate in the energy market, also preferring to have automatic control in their heating system. Authors conclude that recommendation tools are key elements in user-engagement, but they should be supported by additional information and training.